Digital Leadership: Predicting Team Dynamics, Communication Effectiveness, and Team Performance - Subiyanto, Didik; Wahidah, Umi; Septyarini, Epsilandri; Arjuna, Arief Bagus (Journal The Winners, 2024)
Digitalization is essential in modern business organizations, where it transforms the operational framework and increases competitive advantage through the integration of advanced technologies. This transformation enables real-time data analysis, improves communication channels, and automates routine tasks, thereby driving innovation and efficiency that ultimately drives sustainable growth and success in a highly competitive market environment. The research observed the effect of digital leadership on team dynamics, communication effectiveness, and team performance. Data were collected by using a Likert scale questionnaire with 117 individual respondents across various business organizations in Yogyakarta and Banten, Indonesia. Then, the data obtained were analyzed using Structural Equation Modeling (SEM) in AMOS software. The results show that digital leadership has a significant effect on team dynamics and communication effectiveness. In addition, communication effectiveness has been proven to have a significantly positive effect on team performance. However, there is no direct relationship between team dynamics and performance. The results underscore the importance of strengthening digital leadership and communication effectiveness to improve team performance. Organizations should prioritize fostering a collaborative culture through digital platforms, effectively managing conflicts, and ensuring timely communication. Digital leadership should promote a participatory culture, handle conflicts adeptly, and maintain teams motivated through an effective digital approach. Lastly, organizations must provide effective digital communication tools and ensure team members understand how to use them.